1994
DOI: 10.1006/jmla.1994.1039
|View full text |Cite
|
Sign up to set email alerts
|

Mora or Phoneme? Further Evidence for Language-Specific Listening

Abstract: Japanese listeners detect speech sound targets which correspond precisely to a mora (a phonological unit which is the unit of rhythm in Japanese) more easily than targets which do not. English listeners detect medial vowel targets more slowly than consonants. Six phoneme detection experiments investigated these effects in both subject populations, presented with native-and foreign-language input. Japanese listeners produced faster and more accurate responses to moraic than to nonmoraic targets both in Japanese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
1
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 27 publications
9
188
1
3
Order By: Relevance
“…First of all, the vowel /a/ in Japanese-accented / " akto/ is not a phoneme of English (e.g., Ladefoged, 1999), and Japanese listeners perceive it as most similar to the English category />/ (Strange et al, 1998); and while English /b/ and /v/ are confusable at least for mid and low proficiency Japanese learners (Guion et al, 2000), Japanese-accented forms always contained an inserted vowel in coda position, thereby making the syllable structure of the English words permissible in Japanese. Listeners are known to be sensitive to phonological structure in their native language (e.g., Cutler & Otake, 1994Otake, Hatano, & Yoneyama, 1996), and it is unlikely therefore that Japanese listeners could not perceptually distinguish between the non-permissible CVC in /mu:v/ and the permissible CVs in /mu:bu/. As Fais et al (2005) have shown, Japanese listeners judge indeed the non-permissible form keet on a scale of goodness as significantly less good than the permissible form keeto.…”
Section: Experiments 1bmentioning
confidence: 99%
“…First of all, the vowel /a/ in Japanese-accented / " akto/ is not a phoneme of English (e.g., Ladefoged, 1999), and Japanese listeners perceive it as most similar to the English category />/ (Strange et al, 1998); and while English /b/ and /v/ are confusable at least for mid and low proficiency Japanese learners (Guion et al, 2000), Japanese-accented forms always contained an inserted vowel in coda position, thereby making the syllable structure of the English words permissible in Japanese. Listeners are known to be sensitive to phonological structure in their native language (e.g., Cutler & Otake, 1994Otake, Hatano, & Yoneyama, 1996), and it is unlikely therefore that Japanese listeners could not perceptually distinguish between the non-permissible CVC in /mu:v/ and the permissible CVs in /mu:bu/. As Fais et al (2005) have shown, Japanese listeners judge indeed the non-permissible form keet on a scale of goodness as significantly less good than the permissible form keeto.…”
Section: Experiments 1bmentioning
confidence: 99%
“…In French, Catalan, and Spanish, for example, the syllable is the basic metrical unit, and native speakers of these languages use syllabic information in segmentation (Cutler, Mehler, Norris, & Segui, 1986Mehler, Dommergues, Frauenfelder, & Segui, 1981;Pallier, Sebastiân-Gallés, Felguera, Christophe, & Mehler, 1993;Sebastian-Gallés, Dupoux, Segui, & Mehler, 1992). In Japanese, the basic metrical unit is the mora, and accord ingly it appears that Japanese listeners use moraic information in segmentation (Cutler & Otake, 1994;Otake, Hatano, Cutler & Mehler, 1993). Speakers of stress-timed languages like English and Dutch use the rhythmic distinction between strong and weak syllables for segmentation (Cutler & Butterfield, 1992 Zon, & de Gelder, 1996).…”
Section: Segmentation Cues In the Inputmentioning
confidence: 99%
“…Other tasks confirm the robustness of syllabic segmentation in Frcnch (Kolinsky, Morais & Cluytens, 1995;Scgui, Fraucnfelder, & Mchler, 1981). However, target detection docs not show syllabic segmentation in English (Cutler, Mchlcr, Norris & Scgui, 1986) or in Japanese (Otake, Hatano, Cutler, &' Mchlcr, 1993;Cutler & Otake, 1994). Cutler and Norris's (1988) observation that segmentation in English is stress based, by con trast, is supported by patterns of word boundary mispcrceptions (Cutler & Butterfield, 1992) and by evidcncc of activation of monosyllabic words em bedded as strong syllables in longer words (e.g., bone, in trombone; Shillcock, 1990).…”
Section: The Input To the Lexiconmentioning
confidence: 99%